Munasabah dalam Tren Studi Qur’an Kontemporer: Textual Relation dalam Surah al-Ahzab Perspektif Salwa M.S. El-Awwa - Dicky Adi Setiawan, Dicky; M. Sultan Latif Rahmatulloh, Sultan (Mahad Aly Al Fithrah Press, 2022)
This article intends to take a deeper look at how the pattern of mun?sabah offered by Salwa, this is certainly to see how new ideas are carried out and what is a significant difference between the idea of textual relation carried by Salwa and the theory of mun?sabah initiated by his predecessors such as al-Zarkasy, as-Suy?ti and al-Qa???n who are considered the most authoritative figures in the field of 'ul?mu al-Qur?n. Based on research conducted by the authors concluded that the theory used by Salwa is to use a historical-linguistic approach. So it is not only the pattern textually that Salwa tries to analyze the interrelationship but Salwa also sees how the historical context of the decline revelation and in the analysis as a mixture of themes and events that are interconnected between text and context. That is, Salwa basically tried to see how the pattern of mun?sabah in surah al-Ahz?b in answering political, cultural and social context problems in the early higiers in the Arabian Peninsula.